TEKNIK MODELLING TERHADAP KEMAMPUAN TOILET TRAINING ANAK CEREBRAL PALSY TKLB/D-D1 - Istiqomah, Khanif (Jurnal Pendidikan Khusus, 2016)
ABSTRACT This research purpose was to observe whether there was influence of using modeling technique toward toilet training ability of cerebral palsy children in TKLB/D-D1 YPAC Malang. Toilet training ability was a skill which should be possessed by cerebral palsy children in order to be able to control urinating and defecating autonomously. The impact of this deviation to the movement system was caused by damage or handicapped to the brain section relating with motoric function control, cerebral palsy children had obstacle in taking care themselves. In striving to enhance the ability, it was used modeling technique as the learning technique. By modeling, the children could observe and imitate the activity modeled by the model. This research used the kind of pre experiment design. The time applied was 12 times meeting with 10 times intervention. The research design used was one-group pretest posttest design with 6 children as the sample. The data collection method was done by test, observation, and documentation. The data analysis was statistic non parametric using sign test. This research indicated there was score enhancement of toilet training ability to the six cerebral palsy children. The average value of pretest was 4,03 and the average value of posttest was 6,02. From the research result, it was obtained the value of Zh = 2,05 whereas Z table with significant 5% for two sides examination = 1,96. So it could be concluded that Ho was refused and Ha was accepted, it was proved Zh ≥ Z table (2,05 ≥ 1,96). Based on the explanation above, it could be concluded that there was influence of using modeling technique toward toilet training ability of cerebral palsy children in TKLB/D-D1 YPAC Malang.   Keywords: Modeling Technique, Toilet Training